DESAIN ORNAMEN NUSANTARA: KONSEP LANDSCAPE DALAM RELIEF MASJID MANTINGAN - Agus Setiawan; Puri Sulistiyawati (LP2MP3M, INSTITUT SENI INDONESIA SURAKARTA, 2019)
Nusantara’s unique and unique culture has a characteristic position. An interesting thing in the form of visual communication is seeing from the frame of the visual culture that is the concept of landscape in the embodiment of the Mantingan Mosque relief. The reality of the visual culture that occurred in Java walisongo uses the visual culture as the medium of da’wah. Culture in the form of relief with the form of cosmological diagrams with eight distinct angles of sunlight as a form of Surya Majapahit and landscape or landscape with terms with symbols. Landscape in the form of stellar motifs combined bring visual communication symbols. This study aims to: 1) Describe the form of relief that contains the concept of landscape 2) Knowing the concept of landscape in the relief of Mantingan mosque. The method used in this research is a qualitative method, so this research produces descriptive data related to archipelago culture form. The results showed that the Mantingan mosque relief depicts the concept of landscape embodied with stellar motifs in the form of lotus motifs, Meru, stir animals and buildings. Motif stir animals and buildings as the main motif that is considered important surrounded by complex and beautiful motifs of plants.